Relationships between time use and obesity in a representative sample of Americans. Issue 10 (20th August 2016) - Patel, Viral C.; Spaeth, Andrea M.; Basner, Mathias
Abstract : Objective: To provide a nationally representative analysis of time use in America for insight into behaviors associated with obesity. Methods: This study utilized 28, 503 observations of individuals aged 22 to 70 from the American Time Use Survey, a continuous cross‐sectional survey on time use in America. Linear and logistic regressions were performed to analyze sociodemographic characteristics, determine activity participation levels and time spent in activities, understand nonlinear associations between activity time and BMI, and appreciate differences in activity timing between BMI categories. Results: Short and long sleep and work were associated with increased BMI. On weekdays, individuals with obesity were more likely to be working at night and sleeping during the day. They were less likely to participate in sports/exercise/recreation, but those that participated did so for amounts of time not different than normal‐BMI individuals. Those with obesity were more likely to watch television almost all hours of the day. Further differences are detailed for health‐related, sedentary, and household activities. Conclusions: Both short and long sleep, as well as the timing of sleep and work activity, are associated with obesity. Motivation to exercise nonzero amounts may be an appropriate target for intervention. Television is chief among sedentary activities in their association with obesity.